2018
DOI: 10.1007/s11433-017-9169-7
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a monolayer h-BN nanomesh on Rh (111) studied using in-situ STM

Abstract: As a member of the 2D family of materials, h-BN is an intrinsic insulator and could be employed as a dielectric or insulating inter-layer in ultra-thin devices. Monolayer h-BN can be synthesized on Rh (111) surfaces using borazine as a precursor. Using in-situ variable-temperature scanning tunneling microscopy (STM), we directly observed the formation of h-BN in real-time. By analyzing the deposition under variable substrate temperatures and the filling rate of the h-BN overlayer vacant hollows during growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The discovery of graphene opens the way for the study of two-dimensional materials. Subsequently, graphene-like materials, such as two-dimensional hexagonal boron nitride (h-BN), were successfully prepared [5], and its properties were studied theoretically and experimentally [6,7,8]. The spatial structure of monolayer h-BN and graphene was found, they are very similar, but their electronic structure is very different [9].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of graphene opens the way for the study of two-dimensional materials. Subsequently, graphene-like materials, such as two-dimensional hexagonal boron nitride (h-BN), were successfully prepared [5], and its properties were studied theoretically and experimentally [6,7,8]. The spatial structure of monolayer h-BN and graphene was found, they are very similar, but their electronic structure is very different [9].…”
Section: Introductionmentioning
confidence: 99%
“…(3) There is no lattice matching between 2D materials and most metal substrates, which leads to the formation of moiré patterns in 2D material/substrate systems. Experimentally, various moiré patterns between 2D materials and substrates have been observed, including graphene on Ni, Cu, Ru, and Ir; hBN on Cu, Ru, and Rh; MoS 2 on Au; , etc . Studies have shown that moiré patterns can change the growth behavior of 2D materials.…”
mentioning
confidence: 99%